Desirability bias and the effect of financial penalties - Bong, Liek Han (2008)
The objective of this study is to investigate the effect of punishment, in the form of financial penalties, on the desirability bias. The desirability bias leads people to judge desirable outcomes to be more likely, at times leading to unnecessary optimism and dysfunctional risk-taking behaviour.